History, current status and future prospets of geoelectromagnetic research in Ukraine - Burakhovich, Т.; Kushnir, А.; Бурахович, Т.; Кушнір, А. (Київський національний університет імені Тараса Шевченка, 2023)
The current state and prospects for the development of geoelectromagnetic methods are considered. Problems and ways to solve them, new ideas and new tasks are discussed. Modern experimental methods of observations, universal software complexes for their processing, methods of three-dimensional model building of various geological and tectonic units of Ukraine are analyzed. The geological and geophysical interpretation results of regional and local three-dimensional models are shown. Geoelectrical inhomogeneities in the earth's crust and upper mantle of Ukraine, which are characterized by abnormally low and abnormally high values of resistivity, have been revealed. Zones of high conductivity that reach the surface are defined by subvertical heterogeneity and form a galvanically connected system. It spatially correlates with deep faults of various ranks, identified by geological data. The nature of conductivity anomalies at the depth of up to 2.5 km is due to the presence of conductive mineral associations (sulfides, graphite) in the zones of metasomatic processing rocks that lead to the formation of ore mineralization (uranium, gold, rare metals). In the earth's crust at the depths of 5–30 km and the upper mantle of 50–120 km, most likely, traces of the influence of modern mantle fluids are reflected. More and more often, according to the latest data, the nature of anomalies is considered as the result of the joint activity of electronic and ionic conductivity. Conductivity anomalies of the earth's crust and upper mantle indicate possible zones of geodynamic activation, and deep faults are defined by zones of increased permeability through which mantle fluids are unloaded through the lithosphere. In particular, the connection of conductivity anomalies on the territory of Ukraine with the processes of petroleum and ore deposit formation is demonstrated.

Розглянуто сучасний стан та перспективи розвитку геоелектромагнітних методів. Обговорено проблеми та способиїх розв'язання, нові ідеї та завдання. Проаналізовано сучасні експериментальні методики спостережень, універсальні програмні комплекси їх обробки, методику побудови тривимірних моделей різних геолого-тектонічних одиниць України. Наведено результати геолого-геофізичної інтерпретації регіональних та локальних тривимірних моделей. Виявлено геоелектричні неоднорідності у земній корі та верхній мантії України, які характеризуються аномально низькими та аномально високими значеннями електричного опору. Зони високої електропровідності, що виходять на поверхню, визначаються субвертикальною неоднорідністю та утворюють гальванічно пов'язану систему. Вона просторово корелює з глибинними розломами різного рангу, що виділені за геологічними даними. Природа аномалій електропровідності на глибині до 2,5 км зумовлена наявністю асоціації електропровідних мінералів (сульфідів, графіту) у зонах метасоматичної переробки порід, що ведуть до утворення рудної мінералізації (уран, золото, рідкісні метали). У земній корі на глибинах 5–30 км і верхньої мантії 50–120 км, найімовірніше, відображають сліди впливу сучасних мантійних флюїдів. Все частіше за останніми даними природу аномалій розглядають як результат спільної діяльності електронного та іонного типів електропровідності. Аномалії електропровідності земної кори та верхньої мантії свідчать про можливі зони проявів геодинамічної активізації, а глибинні розломи визначаються зонами підвищеної проникності, якими крізь літосферу відбувається розвантаження мантійних флюїдів. Зокрема висвітлено зв'язок аномалій електропровідності на території України з процесами формування нафтогазових і рудних родовищ корисних копалин.
Історія, сучасний стан та напрями розвитку геоелектромагнітних досліджень в Україні
Keywords: геоелектромагнітні методи; інтерпретація тривимірної моделі; аномалії електропровідності; корисні копалини; geoelectromagnetic methods; three-dimensional model interpretation; conductivity anomalies; minerals